C–H and H–H bond activation via ligand dearomatization/rearomatization of a PN3P-rhodium(i) complex. Issue 34 (20th April 2015) - Wang, Yuan; Zheng, Bin; Pan, Yupeng; Pan, Chengling; He, Lipeng; Huang, Kuo-Wei
Abstract : A neutral complex PN 3 P-Rh(i )Cl (2 ) was prepared from a reaction of the PN 3 P pincer ligand (1 ) with [Rh(COD)Cl]2 (COD = 1, 5-cyclooctadiene). Abstract : A neutral complex PN 3 P-Rh(i )Cl (2 ) was prepared from a reaction of the PN 3 P pincer ligand (1 ) with [Rh(COD)Cl]2 (COD = 1, 5-cyclooctadiene). Upon treatment with a suitable base, H–H and Csp 2 –H activation reactions can be achieved through the deprotonation/reprotonation of one of the N–H arms and dearomatization/rearomatization of the central pyridine ring with the oxidation state of Rh remainingi .